2022
DOI: 10.3389/fcell.2021.772380
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Regulation Effects of ESR1/NEDD4L on SLC7A11 in Breast Cancer Under Ionizing Radiation

Abstract: Radiotherapy is one of the most important treatments for breast cancer. Ferroptosis is a recently recognized form of regulated cell death that is characterized by lipid peroxidation. However, whether ionizing radiation (IR) could induce ferroptosis in breast cancer and how it works remain unknown. Bioinformatics analysis were performed to screen ferroptosis-related genes differentially expressed in breast tumor tissue and normal tissue. Then, breast cancer cell lines with different estrogen receptor (ER) pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…An in vitro study showed that NEDD4L inhibits GC proliferation by promoting the ferroptosis of GCs. Consistent with our results, Rui Liu et al found that ESR1 and NEDD4L functioned together after radiation treatment and finally induced ferroptosis in breast cancer cells ( 27 ). This work, as well as other studies, further confirms that the regulation of NEDD4L on cell proliferation is a complex and diverse process.…”
Section: Discussionsupporting
confidence: 93%
“…An in vitro study showed that NEDD4L inhibits GC proliferation by promoting the ferroptosis of GCs. Consistent with our results, Rui Liu et al found that ESR1 and NEDD4L functioned together after radiation treatment and finally induced ferroptosis in breast cancer cells ( 27 ). This work, as well as other studies, further confirms that the regulation of NEDD4L on cell proliferation is a complex and diverse process.…”
Section: Discussionsupporting
confidence: 93%
“… 16 , 18 , 47 , 48 In addition, SLC7A11 imports extracellular cystine into cells to promote glutathione synthesis, thus inhibiting ferroptosis. 49 It was reported that ferroptosis was closely related to several endometrial diseases, such as endometriosis, 50 , 51 repeated implantation failure, 52 and endometrial hyperplasia, 53 and it can act as a therapeutic target for these diseases. Notably, the abnormal biological behaviors of EC patients are tightly associated with the occurrence of adenomyosis and endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…SLC7A11 protein is an important cystine/glutamate transporter that is highly conserved across eukaryotes. 49 Furthermore, the SLC7A11 protein possesses the most conserved region (TIGR00911) of the human solute carrier (SLC) family proteins, which plays an important role in the transportation and binding of proteins, amino acids, peptides and amines. Our findings also revealed that the SLC7A11 protein was localized in the vesicles of human cells.…”
Section: Discussionmentioning
confidence: 99%
“… ESR1/SLC7A11 knockdown significantly promotes radiation-induced ferroptosis in ER-positive breast cancer cells. [ 190 ] Sculponeatin Sculponeatin is a diterpenoid extracted from Isodon sculponeatus. Sculponeatin reduced the expression of ETS1 which is an inducer of SLC7A11-dependent ferroptosis in breast cancer.…”
Section: Slcs In Cancermentioning
confidence: 99%